Act it to grasp it: role play as a catalyst for deeper understanding in active classrooms - Raja Arif, Raja M. Aslam; Abdol Rahim, Abdul Hadi; Hanapi, Suhadiyana; Khairulmaini, Miqdad; Abdul Rasih, Radzi (2025)
In many technical courses, conventional lectures often lead to passive learning, where students struggle to stay engaged and find it difficult to grasp complex concepts. This was a challenge observed in the MEC241 Fluid Mechanics course, where despite clear explanations, students still found it hard to connect theory with real-world application, and frankly, they found the lectures boring. To tackle this, a teaching innovation titled "Act It to Grasp It: Role Play as a Catalyst for Deeper Understanding in Active Classrooms" was introduced. Instead of just listening, students were assigned roles and asked to act out real engineering scenarios. By stepping into the shoes of engineers, technicians, or team leaders, they experienced the content in a more relatable and meaningful way. The classroom was transformed into an active, collaborative space where students engaged with one another, applied concepts through dialogue and decision-making, and developed soft skills like communication and teamwork. Most importantly, they had fun while learning. Feedback collected through a student survey showed strong support for this method. Students reported improved understanding, higher engagement, and greater confidence in expressing their ideas. Many also appreciated the break from traditional lectures and recommended more sessions like this in other topics. This innovation demonstrates that role play is not just a playful activity; it’s a powerful tool to enhance understanding, increase participation, and bring learning to life.